2019
DOI: 10.2196/11280
|View full text |Cite
|
Sign up to set email alerts
|

Internet Access and Hypertension Management Among the Elderly Population: A Nationally Representative Cross-Sectional Survey in China

Abstract: Background Hypertension is a rapidly growing epidemic in China. Yet, it remains inadequately controlled, especially in rural areas. The internet has shown potential for better health management in different settings; however, few studies have investigated its role in hypertension management in China. Objective This study aims to examine the association between internet access and hypertension awareness, treatment, and control among elderly Chinese adults and to investig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…Previous studies using CHARLS cohorts, including one of our own, have demonstrated digital access is associated with better physical health and better outcomes of chronic disease management [39-41]. The national representativeness of CHARLS adds to the robustness of the results, indicating digital devices as a platform for health management.…”
Section: Discussionmentioning
confidence: 77%
“…Previous studies using CHARLS cohorts, including one of our own, have demonstrated digital access is associated with better physical health and better outcomes of chronic disease management [39-41]. The national representativeness of CHARLS adds to the robustness of the results, indicating digital devices as a platform for health management.…”
Section: Discussionmentioning
confidence: 77%
“…Hypertension is one of the most critical factors to cause left ventricular and vascular remodeling ( 22 , 23 ). Furthermore, ventricular remodeling is a risk factor of various severe arrhythmias, as well as sudden mortality ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Comorbidity has been widely observed among chronic disease patients [ 45 ]; for instance, one-half of Chinese people aged 70 or older and one-half to two-thirds of Spanish adults older than 65 have two or more chronic conditions [ 1 ]. As suggested in previous studies [ 11 ], we note three or more cooccurring chronic diseases as an indicator of the severity of chronic disease.…”
Section: Data and Measurementmentioning
confidence: 97%
“…Although mobile health is made possible by widespread mobile technology, younger, more educated, wealthier, and healthier people have an advantage in digital access to m-health; specifically, the affordability, independent usage, and ease of use have been considered as obstacles for elderly users [ 8 , 9 ]. This digital divide has therefore become a main concern in m-health policy [ 10 , 11 ], and it is prevalent in the developing world. For instance, in less developed countries, about 89% of urban households but only 63% of rural ones have a mobile phone [ 12 ].…”
Section: Introductionmentioning
confidence: 99%